Asymptotic Behavior of Global Solution of an Anomalous Gray Scott Model (European Journal of Pure and Applied Mathematics, 2024)
The object of this paper is to prove that existence global and asymptotic behavior of solutions for anomalous coupled reaction diffusion system (Gray Scott model) with homogeneous Neumann boundary conditions. The existence and uniqueness of the local solution are given by the Banach fixed point theorem. However, the asymptotic behavior is investiged by technique semi group estimates and the Sobolev embedding theorem
Keywords: Parabolic system , fractional l Laplacian, global solution, asymptotic behavior